A multi‐layered strategy for COVID‐19 infection prophylaxis in schools: A review of the evidence for masks, distancing, and ventilation. (24th October 2022) - McLeod, Robert S.; Hopfe, Christina J.; Bodenschatz, Eberhard; Moriske, Heinz‐Jörn; Pöschl, Ulrich; Salthammer, Tunga; Curtius, Joachim; Helleis, Frank; Niessner, Jennifer; Herr, Caroline; Klimach, Thomas; Seipp, Martin; et al.
Abstract: Implications for the academic and interpersonal development of children and adolescents underpin a global political consensus to maintain in‐classroom teaching during the ongoing COVID‐19 pandemic. In support of this aim, the WHO and UNICEF have called for schools around the globe to be made safer from the risk of COVID‐19 transmission. Detailed guidance is needed on how this goal can be successfully implemented in a wide variety of educational settings in order to effectively mitigate impacts on the health of students, staff, their families, and society. This review provides a comprehensive synthesis of current scientific evidence and emerging standards in relation to the use of layered prevention strategies (involving masks, distancing, and ventilation), setting out the basis for their implementation in the school environment. In the presence of increasingly infectious SARS‐Cov‐2 variants, in‐classroom teaching can only be safely maintained through a layered strategy combining multiple protective measures. The precise measures that are needed at any point in time depend upon a number of dynamic factors, including the specific threat‐level posed by the circulating variant, the level of community infection, and the political acceptability of the resultant risk. By consistently implementing appropriate prophylaxis measures, evidence shows that the risk of infection from in‐classroom teaching can be dramatically reduced. Current studies indicate that wearing high‐quality masks and regular testing are amongst the most important measures in preventing infection transmission; whilst effective natural and mechanical ventilation systems have been shown to reduce infection risks in classrooms by over 80%.